Computational investigation on the mechanism of oxygen tolerance in the radical SAM enzyme lysine 2,3-aminomutase - Spadoni, Damiano (2022)
The radical S-adenosylmethionine (AdoMet or SAM) enzyme superfamily represents an ensemble of proteins that are able to catalyse biochemical reactions involving organic radical intermediates. These intermediate radicals then undergo a wide range of reactions, many of them difficult to accomplish in the laboratory. The products of such reactions are bioactive compounds of pharmaceutical interest that can be more over used as building blocks for other compounds. Virtually every enzyme belonging to this family is known to be unstable in air due to the requirement for a catalytic, oxygen sensitive [Fe4-S4] cluster that decomposes after oxidative attack by reactive oxygen species (ROS), inactivating the enzyme. The study of these enzymes and their possible application in biotechnology is difficult due to the oxygen sensitivity of the [Fe4-S4] cluster forcing their usage under strictly inert atmosphere. C. subterminale lysine 2,3-aminomutase (CsLAM) is a widely studied radical AdoMet enzyme and a natural oxygen-tolerant variant from B. subtilis (BsLAM) was discovered that catalyses, in presence of air, the interconversion between α- and β-lysine. This project utilised computational methodologies for the assessment of how radical SAM enzymes may manage to shield their FeS cluster from air degradation. Comparison was made of the CsLAM crystal structure with the structural model of oxygen-tolerant BsLAM, here obtained through homology modelling using the 3D structure as its template. Following the validation of the model through PCA, both the CsLAM and the BsLAM enzyme structures were compared and molecular dynamics simulations were used to identify different ways the two enzymes might deal with oxygen. The tunnel searching software CAVER was used to identify those amino acid residues that could obstruct oxygen flow due to their size or their ability to trap oxygen in BsLAM. Quantum mechanics calculations were then performed on the [Fe4-S4] sub-system to retrieve information about the difference in the electrostatics governed by the protein environment. The difference in electrostatics could account for different redox potentials in the two enzymes by making the BsLAM less prone to oxidation by ROS. A selection of amino acid residues were identified as likely to affect the redox potential and mutants of the CsLAM bearing such residues were created. The observation of their dipole moment suggested that the double mutation H131Y/A138S could positively affect the oxygen tolerance in the enzyme.